The English Language Needs of Hospitality and Hotel Management Students at a Saudi University: Integrating Agile Philosophy into ESP - Sulaiman Alhumaidan, Ghadeer; Mohammed Alghamdi, Ahmed (International Journal of English Language Education, 2023)
The English language plays a vital role in tourism, particularly in hospitality and hotel management. As a result, there is a need to investigate the English language requirements of this industry and train employees who can perform well both professionally and competently. This prompted us to investigate one of the Hospitality and Hotel Management (HHM) programs at King Abdulaziz University’s (KAU) College of Tourism. This program is responsible for training graduate students who will work in the HHM sector. As a result, the researcher’s aims in this study are to investigate the English language needs of Hospitality and Hotel Management program, and to introduce Agile English for Specific Purposes (AESP) as a new approach to teaching English in the field of English for Specific purposes. This research used a mixed-method approach to gather quantitative and qualitative data through a questionnaire, interviews and book evaluation. The study sample consisted of fifteen graduate and undergraduate students, five teachers from the HHM program at the same faculty, and six employees from different HHM sectors. According to the findings of this study, speaking was the most needed skill, as well as the way the current HHM program did not meet the English needs of the students. Moreover, this study presented AESP as a solution that combined all of the required needs into one.